0 like 0 dislike
Write the quadratic equation in factored form
x 2 + x - 12 = 0
by

2 Answers

0 like 0 dislike
(x-3)(x+4)=0

Step-by-step explanation:

We want to rewrite the following quadratic equation in factor form

[tex] {x}^{2} + x - 12 = 0[/tex]

What's a quadratic equation?

Equations with second degree are called quadratic equations.The standard form of a quadratic equation is

- ax²+bx+c=0

How to factor the quadratic equation?

The steps of factoring the quadratic are as follows:

- Figure out two terms whose sum is 1 and product is -12
- break up the middle term
- group if required
- factor the common terms

Factoring the quadratic:

[tex] {x}^{2} + x - 12 = 0 \\ \implies {x}^{2} + 4x - 3x - 12 = 0 \\ \implies x(x + 4) - 3(x + 4) = 0 \\ \implies \boxed{(x - 3)(x + 4) = 0}[/tex]

Hence, the factored form of the quadratic equation is (x-3)(x+4)=0
by
0 like 0 dislike
- x²+x-12=0
- x²+4x-3x-12=0
- x(x+4)-3(x+4)=0
- (x-3)(x+4)=0

Zeros are 3 and -4
by
Welcome to AskTheTask.com, where understudies, educators and math devotees can ask and respond to any number related inquiry. Find support and replies to any numerical statement including variable based math, geometry, calculation, analytics, geometry, divisions, settling articulation, improving on articulations from there, the sky is the limit. Find solutions to numerical problems. Help is consistently 100 percent free!

Questions

No related questions found